2023
DOI: 10.1186/s12933-023-02031-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive detection of early microvascular changes in juveniles with type 1 diabetes

Klaudia Bogusz-Górna,
Adriana Polańska,
Aleksandra Dańczak-Pazdrowska
et al.

Abstract: Aims/Hypothesis The study aimed to assess the usefulness of capillaroscopy and photoplethysmography in the search for early vascular anomalies in children with type 1 diabetes. Methods One hundred sixty children and adolescents aged 6–18, 125 patients with type 1 diabetes, and 35 healthy volunteers were enrolled in the study. We performed a detailed clinical evaluation, anthropometric measurements, nailfold capillaroscopy, and photoplethysmography.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…They showed that male participants had lower subpapillary venous plexus visibility scores, but other capillary parameters did not differ between the sexes. Similarly, no gender differences in capillaroscopic parameters were found in a study by Bogusz-Górna et al in a group of children and adolescents with type 1 diabetes [73]. It should be noted that in these studies, a qualitative approach in analyzing the capillaroscopy results was used, while we had the advantage of performing a quantitative description of the capillaries.…”
Section: Discussionmentioning
confidence: 87%
“…They showed that male participants had lower subpapillary venous plexus visibility scores, but other capillary parameters did not differ between the sexes. Similarly, no gender differences in capillaroscopic parameters were found in a study by Bogusz-Górna et al in a group of children and adolescents with type 1 diabetes [73]. It should be noted that in these studies, a qualitative approach in analyzing the capillaroscopy results was used, while we had the advantage of performing a quantitative description of the capillaries.…”
Section: Discussionmentioning
confidence: 87%
“…Reports published to date on the relationship between skin microvascular parameters and metabolic control in patients with T1D have not been consistent [7,52,58,60,[63][64][65]. Some studies have shown that cutaneous microvascular reactivity is independent of metabolic status reflected by HbA 1c values [52,58,60,66]. Meanwhile, in a group of adult patients, Jorneskog et al [64] showed significant differences in capillary flow between patients with poor and good metabolic control regardless of diabetes duration.…”
Section: Metabolic Controlmentioning
confidence: 99%